THE ANALYSIS OF PATIENT CHARACTERISTICS OF COMPLIANCE IN THE USE OF METADONE THERAPY IN THE BANGKONG RIVER REGIONAL MENTAL HEALTH CLINIC OF PONTIANAK IN THE PERIOD OF 2020-2021 - Prisilla, Salma; Nurmainah, Nurmainah; Andrie, Mohamad (Journal Pharmacy Of Tanjungpura, 2023)
ABSTRACT  Compliance with Injecting Drug Users (IDUs) in Methadone Maintenance Therapy is crucial during rehabilitation. However, many IDUs still do not comply with methadone therapy. As a result, the patient may once more experience withdrawal symptoms. The purpose of this study was to examine the percentage of patient compliance and the impact of patient's age, education, and occupation on compliance with the use of methadone therapy at Sungai Bangkong Region Psychiatric Hospital, Pontianak. The research method used is observational research with an analytical cohort study design. The data were taken from patient's medical record, which includes the patient's medical record number and patient characteristics such as age, gender, last education, occupation, and the number of days the patient received the drug. The collected medical record data is then analyzed using the Chi-Square analysis method. The results showed that the respondents had a high level of compliance with a percentage of 85.7%. Compliant patients are dominated by patients in the 20-40 age range, with college as their last education, and working as laborers. The results of the Chi-square test analysis showed the impact of age, education, and occupation on compliance, with values of p = 0.462; p=1,000; p=1,000, respectively. This study concludes that characteristics like age, education, and occupation had no impact on patient compliance in undergoing Methadone Maintenance Therapy.  Keywords: Compliance, Injecting Drug Users, Methadone Maintenance Therapy